2000
DOI: 10.1023/a:1004096330727
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Allozyme electrophoresis of four sibling parthenogenetic Caucasian rock lizards Darevskia unisexualis, D. uzzelli, D. sapphirina, and D. bendimahiensis found seven clones and five variable loci. The data supported the hypothesis that D. raddei and D. valentini are the parental species of all four parthenogens. Variation patterns in Darevskia were summarized. Species that originated from a single F1 typically consisted of one widespread clone with a few rare clones. Species with multiple origins displayed varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Potentially, one could explain polymorphism within the parthenogens by the aggregation of de novo mutations. However, additional evidence caused multiple authors to interpret genetic variation within the parthenogens as polyclonality, i.e., descent from different F1 hybrids [ 48 , 49 , 51 , 52 , 54 , 55 ]; but see [ 53 ]. In our study, the presence of multiple and fixed differences between D. armeniaca and D. dahli is probably not solely the result of accumulated mutation; at least such extent of divergent phenotypic evolution is unknown in vertebrate parthenogens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Potentially, one could explain polymorphism within the parthenogens by the aggregation of de novo mutations. However, additional evidence caused multiple authors to interpret genetic variation within the parthenogens as polyclonality, i.e., descent from different F1 hybrids [ 48 , 49 , 51 , 52 , 54 , 55 ]; but see [ 53 ]. In our study, the presence of multiple and fixed differences between D. armeniaca and D. dahli is probably not solely the result of accumulated mutation; at least such extent of divergent phenotypic evolution is unknown in vertebrate parthenogens.…”
Section: Discussionmentioning
confidence: 99%
“…To check for contamination and pipetting error, a negative control (reagents only) was used for each extraction procedure and PCR. Two different primer pairs (H15915 – L15369 and H15488 – L15153, [ 45 , 48 ]) were used for amplification of a 683 bp fragment of the cytochrome b mitochondrial gene [ 24 , 45 , 46 ]. The PCR conditions were as follows: 20 μl total volume, with 2–4 μl template DNA, 1 U of GoTaq Flexi DNA Polymerase (Promega), 1X GoTaq Green Flexi DNA Polymerase buffer, 1 mM of MgCl2, 0.2 mM of each dNTP and primer concentrations at 0.1 μM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, it has been found that parthenogenesis in reptiles is known in less than 0.46% of species ( Fujita and Moritz 2009 ). In general, cytological, genetic, morphological and ecological studies have shown that parthenogenetic lizards of the genus Darevskia , namely D. dahli (Darevsky, 1957), D. rostombekowi (Darevsky, 1957), D. uzzelli (Darevsky et Danielyan 1977), D. armeniaca (Méhely, 1909), D. unisexualis (Darevsky, 1966), D. sapphirina (Schmidtler et al, 1994) and D. bendimahiensis (Schmidtler et al, 1994) have originated as a result of natural hybridisation between bisexual parental species ( Darevsky 1958 , Darevsky 1967 , Uzzell and Darevsky 1975 , Macculloch et al 1997 , Fu et al 1999 , Fu et al 2000a , Fu et al 2000b , Murphy et al 2000 , Kupriyanova 1999 , Martirosian et al 2002 , Martirosian et al 2003 , Malysheva et al 2007a , Malysheva et al 2007b ).…”
Section: Introductionmentioning
confidence: 99%